25-Hydroxyvitamin D levels in patients treated with high-dosage ergo- and cholecalciferol. Issue 2 (February 1977) - Gertner, J M; Domenech, M
Abstract : 25-Hydroxyvitamin D (25-OHD) levels were measured in 39 patients with metabolic bone disease or hypoparathyroidism who had been treated with a constant high dose of vitamin D2 or D3 for at least 12 weeks. Plasma 25-OHD levels rose with increasing dosage, the relationship between dose and plasma level being approximately linear whether or not the dose was expressed on a weight-corrected basis. A therapeutic range of 25-OHD to be expected when patients with these conditions are treated with vitamin D has been established. There may be certain exceptions in which plasma 25-OHD levels within the range are associated with either an inadequate response to treatment or, conversely, the hypercalcaemia of vitamin D toxicity. There was no correlation between plasma calcium level and 25-OHD concentration in the group of patients studied. There was also no difference between the dose/25-OHD relationship of patients treated with vitamin D2 and that of patients receiving vitamin D3. Ten patients were started on treatment with large doses of vitamin D during the period of the study. The rate of rise of plasma 25-OHD was followed during treatment. The incremental rise in 25-OHD was calculated at the end of the first week of treatment in terms of dose per unit body weight. The rate of rise of plasma 25-OHD level was highly correlated with the dose used. Plasma 25-OHD levels after one weeks' treatment were only 15-20% of the expected steady-state level on the same dosage. The importance of a high priming dose when a rapid response is needed is thus emphasised.